The Influence of Leadership Style and Work Facilities on Discipline and Its Impact on Employee Performance - M. Aris; M. Zahari; Osrita Hapsara (Dinasti Publisher, 2024)
The purpose of this study is to: 1) Find out the leadership style of regional employees, work facilities and follow-up to describe discipline with performance; 2) The purpose of this study is to test the direct and indirect influence of leadership style and work facilities on employee discipline; 3) This study was developed with the aim of testing how leadership style and work facilities affect employee performance both directly and indirectly; 4) The influence of discipline on employee performance; 5) Testing Leadership Style and Work Facilities on Employee Performance (Through Discipline). This study was conducted at the Regional Finance and Asset Agency of Tanjung Jabung Barat Regency, Jambi Province, Indonesia, with a research sample of 88. This analysis method uses the Path Analysis tool, and hypothesis testing uses the F test & t test using SPSS - V.22. Findings from the analysis; 1) Very good status in leadership style and work facilities, very good / very high in discipline practices and employee performance; 2) Discipline is influenced by leadership style and work facilities directly or indirectly. Simultaneously, the results of the significance test show that leadership style and work facilities affect discipline; 3) The results of the hypothesis testing are also known simultaneously to show that leadership style and work facilities have a significant influence on employee performance. Likewise, partially, leadership style and work facilities have a significant influence on employee performance; 4) Discipline has a significant influence on employee performance; and 5) Leadership style and work facilities through discipline affect employee performance.